2010
DOI: 10.1007/s00442-010-1777-z
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of the invasive shrub Lonicera maackii increase mortality and alter behavior of amphibian larvae

Abstract: Water-soluble phytochemicals produced by invasive plants may represent novel elements of invaded ecosystems that can precipitate a variety of direct and indirect effects on native organisms. Phenolic compounds in particular are a common plant defense, and these compounds may have disproportionate impacts on amphibians compared to other taxa. We coupled an exploration of invasive plant extract effects on larvae of four amphibian species (the salamander Ambystoma maculatum, the toad Anaxyrus americanus, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 34 publications
2
72
2
Order By: Relevance
“…Lonicera maackii is native to Asia and first introduced to North America in 1897 (Luken and Thieret 1996). The invasion of L. maackii across the eastern and midwestern US is associated with reduced cover (Hutchinson and Vankat 1997), richness, and abundance (Collier et al 2002) of native understory vegetation, as well as important changes in the abundance and behavior of native organisms (Allan et al 2010;Conley et al 2011;Dutra et al 2011;Mattos and Orrock 2010;McKinney and Goodell 2010;Watling et al 2011a). Lonicera maackii invasion may be promoted by the widespread dispersal of its seeds by frugivorous birds (Bartuszevige and Gorchov 2005;Watling and Orrock 2010) and its success in direct competition with understory species (Gorchov and Trisel 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Lonicera maackii is native to Asia and first introduced to North America in 1897 (Luken and Thieret 1996). The invasion of L. maackii across the eastern and midwestern US is associated with reduced cover (Hutchinson and Vankat 1997), richness, and abundance (Collier et al 2002) of native understory vegetation, as well as important changes in the abundance and behavior of native organisms (Allan et al 2010;Conley et al 2011;Dutra et al 2011;Mattos and Orrock 2010;McKinney and Goodell 2010;Watling et al 2011a). Lonicera maackii invasion may be promoted by the widespread dispersal of its seeds by frugivorous birds (Bartuszevige and Gorchov 2005;Watling and Orrock 2010) and its success in direct competition with understory species (Gorchov and Trisel 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Honeysuckle was first introduced to North America from Asia in the 1800s as an ornamental plant and since then has become a dominant plant in many forest and shrubland systems, particularly in the eastern US (Hutchison and Vankat 1997). Numerous studies have documented the negative consequences of honeysuckle to native plants (Gould andGorchov 2000, Collier et al 2002), animals (Schmidt & Whelan 1999, Watling et al 2011), ecosystem processes (Ehrenfeld et al 2001, Ehrenfeld 2003, ecological services such as pollination (McKinney & Goodell 2010), and even human health (Allan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, laboratory experiments conducted by Watling et al (2011a) showed that extracts from L. maackii increased mortality in American toad tadpoles and increased surfacing trips by American toad and plains leopard frog (Lithobates blairi) tadpoles. Watling et al (2011b) reported lower amphibian species richness and evenness in forested areas invaded by L. maackii.…”
Section: Amphibians and Mammalsmentioning
confidence: 97%